Fintech Untuk Semua Menjembatani Kesenjangan Akses Keuangan di Pedesaan Indonesia 2025 - Nur Aima Shafie1; Saiful Bakhri; Risa Umami (Tasharruf : Journal of Islamic Economics and Business, 2025)
This study analyzes the strategic role of fintech in addressing the gap in access to rural finance in Indonesia in 2025, using a qualitative approach by applying the literature review method. Structural gaps remain critical (rural financial inclusion index: 75.7% vs urban 89.2%), triggered by a triad of digital infrastructure problems(22% of villages have unstable electricity), dual literacy (only 35% understand fintech products), and gender gap (female account ownership: 74.3%).Through a qualitative approach, the 2026-2030 Agenda focuses on regulatory harmonization.blockchain, gender affirmation (40% quota of female LKD agents), expansiongreen fintechfor renewable energy, as well as the construction of 300 4G/5G towers and trainingcyber hygiene20,000 agents. Research concludes that rural financial justice can only be achieved through the integration of adaptive regulation-inclusive infrastructure-local wisdom-based education,with risk mitigationdigital colonialism and ESG principles as pillars of sustainability.